Pengembangan Kursi Laboratorium Komputer Teknik Industri Dengan Metode Pendekatan Ergonomi - Suwanto; Wibowo, Moh. Muhyidin Agus; Kalista, Anggia; Sanjaya, Krishna Tri (Universitas PGRI Ronggolawe, 2022)
Static activity and dynamic activity are used as the basis for measuring body size. Ergonomics related to the dimensions of the human body is anthropometry. Anthropometry is needed as a guide in the implementation of adjusting the sizes of work equipment and tools, furniture, clothing, and all equipment that is directly related to humans. Anthropometry is related to measuring the state and physical characteristics of humans from the size of the head, hands, body, hips, to feet. The measurement data is used as a reference for product development according to user needs. Industrial Engineering UNIVERSITY OF PGRI RONGGOLAWE TUBAN (UNIROW) has a computer laboratory with a class area of 99 m², with a capacity of 60 students. One of the computer lab facilities is a laboratory chair that is currently used in the Industrial Engineering computer laboratory at the University of PGRI Ronggolawe Unirow Tuban. It is a chair with an iron frame, a seat mat, and a backrest. The dimensions of the lab chair used today have a chair leg height of 50 cm, a seat width of 50 cm, a backrest height of 60 cm.